Magic sets with full sharing - Azevedo, Paulo J. (1997)
In this paper we study the relationship between tabulation and goal-oriented bottom-up evaluation of logic programs. Differences emerge when one tries to identify features of one evaluation method in the other. We show that to obtain the same effect as tabulation in top-down evaluation, one has to perform a careful {\em adornment} in programs to be evaluated bottom-up. Furthermore we propose an efficient algorithm to perform forward subsumption che cking over adorned {\em magic facts}.